Impact of PD-L1 and PD-1 Expression on the Prognostic Significance of CD8+ Tumor-Infiltrating Lymphocytes in Non-Small Cell Lung Cancer - Munari, Enrico; Marconi, Marcella; Querzoli, Giulia; Lunardi, Gianluigi; Bertoglio, Pietro; Ciompi, Francesco; Tosadori, Alice; Eccher, Albino; Tumino, Nicola; Quatrini, Linda; Vacca, Paola; Rossi, Giulio; et al. (Frontiers in Immunology, 2021)
The immune infiltrate within tumors has proved to be very powerful in the prognostic stratification of patients and much attention is also being paid towards its predictive value. In this work we therefore aimed at clarifying the significance and impact of PD-L1 and PD-1 expression on the prognostic value of CD8+ tumor infiltrating lymphocytes (TILs) in a cohort of consecutive patients with primary resected non-small cell lung cancer (NSCLC). Tissue microarrays (TMA) were built using one representative formalin fixed paraffin embedded block for every case, with 5 cores for each block. TMA sections were stained with PD-L1 (clone SP263), PD-1 (clone NAT105) and CD8 (clone SP57). Number of CD8+ cells per mm2 were automatically counted; median, 25th and 75th percentiles of CD8+ cells were used as threshold for statistical clinical outcome analysis and evaluated in patients subgroups defined by expression of PD-L1 and PD-1 within tumors. We found an overall strong prognostic value of CD8+ cells in our cohort of 314 resected NSCLC, especially in PD-L1 negative tumors lacking PD-1+ TILs, and demonstrated that in PD-L1 positive tumors a higher density of CD8+ lymphocytes is necessary to improve the prognosis. Our data strengthen the concept of the importance of the assessment and quantification of the immune contexture in cancer and, similarly to what has been carried on in colorectal cancer, promote the efforts for the establishment of an Immunoscore for NSCLC for prognostic and possibly predictive purposes.